2014
DOI: 10.1002/14651858.cd007470.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation for prevention of mortality in adults

Abstract: Vitamin D3 seemed to decrease mortality in elderly people living independently or in institutional care. Vitamin D2, alfacalcidol and calcitriol had no statistically significant beneficial effects on mortality. Vitamin D3 combined with calcium increased nephrolithiasis. Both alfacalcidol and calcitriol increased hypercalcaemia. Because of risks of attrition bias originating from substantial dropout of participants and of outcome reporting bias due to a number of trials not reporting on mortality, as well as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
346
3
21

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(395 citation statements)
references
References 467 publications
12
346
3
21
Order By: Relevance
“…Кроме того, систематический обзор выполненный на основании анализа 159 рандомизированных клиниче-ских исследований, показал, что регулярный прием вита-мина D снижал смертность среди людей пожилого возрас-та [46].…”
Section: витамин D и остеопорозunclassified
“…Кроме того, систематический обзор выполненный на основании анализа 159 рандомизированных клиниче-ских исследований, показал, что регулярный прием вита-мина D снижал смертность среди людей пожилого возрас-та [46].…”
Section: витамин D и остеопорозunclassified
“…Nonetheless, low plasma 25hydroxy vitamin D concentration is associated with high arterial blood pressure and the risk of hypertension [5] , and therefore a constant therapy of vitamin D, either alone or combined with calcium, for the prevention and treatment of osteoporosis, in the absence of explicit risk factors for vitamin D deficiency, appears to be inappropriate [6,7] . Indeed, this therapy may provoke a significant rise in gastroin testinal symptoms and renal diseases [6] .…”
Section: The Medical Problemmentioning
confidence: 99%
“…Yet despite the dangers, nearly half of all over50s continue to use these supplements [8] . The effect of vitamin D on the mortality of the elderly is in fact very odd: Whereas vitamin D3 seems to decrease mortality, vitamin D2, alfacalcidol and calcitriol apparently have no beneficial effects at all [6] , and may even provoke hypercalcaemia; moreover, if vitamin D3 is administered together with calcium supplementation, the risk of nephrolithiasis is increased [7] . However, the current use of vitamin D by elderly people as a strategy for the prevention of hip fracture could be promoted just for its effects on muscular atrophy.…”
Section: The Medical Problemmentioning
confidence: 99%
“…A separate meta-analysis concluded that Vitamin D3 supplementation appeared to reduce mortality only in older female subjects living either independently or in institutional care [15].…”
Section: Risk Versus Benefitmentioning
confidence: 99%